Nurturing Innovative Work Behavior in Higher Education: The Roles of Job Autonomy and Organizational Support - Michael, Solano; Saka, Samuel; Sabuaya, Dison (Journal of Current Research In Multidisciplinary, 2025)
In the rapidly evolving landscape of global higher education, characterized by digital disruption and shifting pedagogical paradigms, the ability of an institution to innovate has become a primary determinant of its long-term sustainability and academic excellence. At the center of this transformative process is Innovative Work Behavior (IWB), a multifaceted construct that encompasses the generation, promotion, and implementation of novel ideas by academic staff to enhance organizational effectiveness. Despite its critical importance, many higher education institutions (HEIs) struggle to move beyond traditional, bureaucratic management styles that often stifle individual creativity. This study aims to fill a significant gap in the literature by empirically investigating the influence of two key organizational determinants Job Autonomy and Perceived Organizational Support (POS) on the innovative work behavior of educators within the higher education sector. Drawing upon Job Characteristics Theory and Social Exchange Theory, this research utilizes a quantitative approach with an explanatory research design. Data were collected through a structured online survey from a diverse sample of 350 full-time faculty members and academic staff across several prominent universities. The research instrument utilized validated scales to measure the latent constructs, and the data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). This method was selected for its robustness in testing complex structural relationships and its high predictive power in organizational behavior studies.